The decreased of Streptococcus Mutans growth after topical application of phosphopeptide amorphous calcium phosphate paste - Araf, Tika Faradina; Gartika, Meirina; Dewi, Warta (Padjadjaran Journal of Dentistry, 2011)
Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) paste is a topical application substance that consisted of a series of milk derivative peptide as a result of phosphorylation and has an antibacterial activity. The objective of this research was to find out the difference of Streptococcus mutans growth before and after CPP-ACP paste given topically to child's teeth. The method of the research was a quasi-experiment. Research samples were 10 students of MI Al Falah Islamic Boarding School, Jatinangor, West Jawa Indonesia and collected with purposive sampling technique. This research used dental plaque from child's teeth before and after applicated by CPP-ACP paste. The plaque was cultivated in selective media Tryptone Yeast Cysteine Sucrose Bacitracin (TYCSB) with repeated twice. Streptococcus mutans colony in TYCSB were counted by Stuart colony counter and statistically analyzed based on paired t-test. The results showed the average of Streptococcus mutans growth before applicated CPP-ACP paste was 57.05, whereas after applicated CPP-ACP paste for 1 days was 9.4; for 3 days was 2.85, and for 14 days was 1.7 colony. The research concluded that there was a decrease of Streptococcus mutans growth in isolate plaque after CPP-ACP paste topically given to child's teeth.